MICROSOFT VISUAL BASIC 6.0 APPLICATION OF LESSONS IN MATHEMATICAL PROCESS FOR ADDITION, subtraction, multiplication UP WITH PROCESS FOR DISTRIBUTION OF PRIMARY LEVEL - Susanti susanti; EKO HADIYANTO SSi, MMSI (Jurnal Sistem Informasi, 2002)
Scientific writing is about the making of applications ie applications of maths to the children. Used mathematical process is a process of Addition, subtraction, Multiplication, and division. Programs created using Microsoft Visual Basic 6.0. Start by making the application in estimating needs, designing the look and then make the source code for the application.Visual Basic 6.0 applications in mathematics lessons are designed and manufactured with attractive displays that can be easily used by children.